2022
DOI: 10.1111/epi.17356
|View full text |Cite
|
Sign up to set email alerts
|

Risk of hospitalization and death for COVID‐19 in persons with epilepsy over a 20‐month period: The EpiLink Bologna cohort, Italy

Abstract: Objective Data on COVID‐19 outcomes in persons with epilepsy (PWE) are scarce and inconclusive. We aimed to study the risk of hospitalization and death for COVID‐19 in a large cohort of PWE from March 1, 2020 to October 31, 2021. Methods The historical cohort design (EpiLink Bologna) compared adult PWE grouped into people with focal epilepsy (PFE), idiopathic generalized epilepsy (PIGE), and developmental and/or epileptic encephalopathy (PDEE), and a population cohort m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
1
13
0
1
Order By: Relevance
“…1 Early studies on whether SARS-CoV-2 infection could cause seizures and resultant epilepsy and whether COVID-19 and its sequelae were more prevalent or severe in persons with preexisting epilepsy were difficult to interpret because SARS-CoV-2 antigen tests had not yet been developed or widely deployed. [1][2][3] In 2020 and 2021, it was observed that COVID-19 patients hospitalized with severe pulmonary signs sometimes had encephalopathy, but acute seizures and status epilepticus appeared to be relatively uncommon. [4][5][6] Taquet et al questioned whether patients with COVID-19 were more likely than controls to develop seizures or epilepsy.…”
Section: Commentarymentioning
confidence: 99%
“…1 Early studies on whether SARS-CoV-2 infection could cause seizures and resultant epilepsy and whether COVID-19 and its sequelae were more prevalent or severe in persons with preexisting epilepsy were difficult to interpret because SARS-CoV-2 antigen tests had not yet been developed or widely deployed. [1][2][3] In 2020 and 2021, it was observed that COVID-19 patients hospitalized with severe pulmonary signs sometimes had encephalopathy, but acute seizures and status epilepticus appeared to be relatively uncommon. [4][5][6] Taquet et al questioned whether patients with COVID-19 were more likely than controls to develop seizures or epilepsy.…”
Section: Commentarymentioning
confidence: 99%
“…Estos pacientes nunca tuvieron un episodio convulsivo definido antes de la infección. La electroencefalografía se realizó a los pacientes porque tenían encefalopatía o había tenido algún (30) episodio similar a una convulsión con el cual se valoró la actividad epileptiforme .…”
Section: Convulsionesunclassified
“…SARS‐CoV‐2 is known to directly affect the central nervous system, with high rates of neurological and psychiatric complications 11,12 . There is some evidence that people with epilepsy are at increased risk of COVID‐19 hospitalization and COVID‐19 death 13–16 . This may be in part due to the increased proportion of people with epilepsy with comorbidities, such as dementia and intellectual disability, that increase the risk of severe COVID‐19 13,16 …”
Section: Introductionmentioning
confidence: 99%
“…11,12 There is some evidence that people with epilepsy are at increased risk of COVID-19 hospitalization and COVID-19 death. [13][14][15][16] This may be in part due to the increased proportion of people with epilepsy with comorbidities, such as dementia and intellectual disability, that increase the risk of severe COVID-19. 13,16 SARS-CoV-2 vaccines have significantly improved COVID-19 outcomes.…”
Section: Introductionmentioning
confidence: 99%